How effective were government food box schemes for those who were shielding during the first wave of the COVID-19 pandemic in the United Kingdom? Local and national stakeholder perspectives - Hannah Lambie-Mumford; Rachel Loopstra; Katy Gordon (Cambridge University Press, 2023)
Abstract Objective: In spring 2020, governments across the UK put in place food box schemes to protect access to food for the population told to 'shield' from COVID-19 (i.e. not leave their house for any reason). This article explores the design, implementation and impact of food box schemes intended to regularly provide a week's worth of food for individuals who were shielding. Design: Interviews and workshops with national and local stakeholders over summer 2020 to autumn 2021. Setting: England, Northern Ireland, Scotland and Wales. Participants: National and local government and NGO stakeholders involved in food response during the COVID-19 pandemic. Results: Local authorities played a crucial role, implementing and supplementing the national provision of food box schemes. Three key shortcomings of the schemes were identified: coverage, contents and accessibility. In England and Wales, the scheme only provided food for shielding individuals, not their household members. Across the schemes, box contents were criticised for not containing sufficient amounts of fresh or healthy food and for not being able to meet individual dietary requirements. They were also inaccessible for people who required support with lifting or preparing food. Conclusions: The inadequacy of shielding food box schemes may have undermined people's ability to shield during the first UK lockdown. The COVID-19 pandemic required rapidly implemented policy responses, but these findings underscore the importance of universal provision and nutrition, physical accessibility and cultural food needs when formulating public health nutrition interventions.